2020
DOI: 10.1039/c9nj04216d
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic silver and silver oxide hybrid nanoparticles: a potential antimicrobial against multi drug-resistant Pseudomonas aeruginosa

Abstract: Ag/Ag2O NPs synthesized using K. abolonga exhibited antimicrobial activity along with carbenicillin against MDR P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…D’Lima et al reported Ag/Ag 2 O NPs by employing a biosynthesis approach using a novel strain of Kitasatospora albolonga . 316 The microscopic and structural analysis of obtained material reveals a spherical shaped Ag–Ag 2 O hybrid core–shell (Ag 2 O@Ag) structured NPs ( Figure 14 a). Though these hybrid NPs had shown antimicrobial activity independently, however, when combined with carbenicillin, it showed an improved toxic synergetic effect on multi-drug-resistant P. aeruginosa (MDRP) at low concentrations ( Figure 14 b).…”
Section: Antibacterial and Antiviral Properties Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…D’Lima et al reported Ag/Ag 2 O NPs by employing a biosynthesis approach using a novel strain of Kitasatospora albolonga . 316 The microscopic and structural analysis of obtained material reveals a spherical shaped Ag–Ag 2 O hybrid core–shell (Ag 2 O@Ag) structured NPs ( Figure 14 a). Though these hybrid NPs had shown antimicrobial activity independently, however, when combined with carbenicillin, it showed an improved toxic synergetic effect on multi-drug-resistant P. aeruginosa (MDRP) at low concentrations ( Figure 14 b).…”
Section: Antibacterial and Antiviral Properties Of Nanomaterialsmentioning
confidence: 99%
“…Inset: Zone of inhibition. Reproduced with permission from ref ( 316 ). Copyright 2020 The Royal Society of Chemistry.…”
Section: Antibacterial and Antiviral Properties Of Nanomaterialsmentioning
confidence: 99%
“…AgNPs were shown to have antimicrobial properties against several pathogenic microorganisms ( Scandorieiro et al., 2016 ; Figueiredo et al., 2019 ), including Pseudomonas aeruginosa ( Liao et al., 2019 ; D’Lima et al., 2020 ). This bacterium can be found in various environments, such as hospitals, natural resources, and water supply systems ( Dobias and Bernier-Latmani, 2013 ; Anversa et al., 2019 ; Esmaeili et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 60 ] Although silver oxide NPs have not yet been tested against viruses, they are promising antiviral candidates owing to their known antimicrobial activity. [ 230–232 ] Furthermore, Minoshima et al. demonstrated the efficacy of Cu 2 O particles (0.5–5 µm) and silver ionic compounds (AgNO 3 and Ag 2 O) against the H1N1 influenza virus with the denaturation of viral receptor proteins, such as hemagglutinin (HA).…”
Section: Ceramics Against Virusesmentioning
confidence: 99%